ESTIMATION OF EFFICIENCY OF COLLAGEN AND BIOLOGICAL GLUE AT DUODENAL FISTULA IN EXPERIMENT - R. R. Ishtukov; M. A. Nartailakov; V. S. Panteleev; V. V. Rezyapov (Креативная хирургия и онкология)
Introduction. One of the worst complication of different surgical diseases of abdominal cavity organs and of performed, on that regard, operational interventions, are intestinal festulas including without limitation deodenum fistulas. Longterm experience of surgical treatment of patients with unformed duodenal and high enteric fistulas show that it is feasible to have a clear surgical tactics with account of location level and type of fistulas, their quantity, volume of sarcous reduction, peritonitis and multi-organ failure syndrome. In this regard, the objective of this research is to find optimal surgical tactics and to determine the most effective method of treating duodenum fistulas of various causation.Materials and methods. Experimental work was carried out under conditions of experimentally formed intestinal fistula in rabbits of “Shinshilla” breed. After formation of fistula the animals were divided into 3 groups based on the method of removing artificially installed duodenal fistula: sealing through Albert — Schmieden — Lembert suture without fastening of suture line; sealing through fastening of intestinal suture with biological surgical glue; sealing through fastening with swine dermal collagen. Mechanical constancy of the sutures was measured with pneumocompression of sealed intestinal tract areas as well as with morphological study of surgical wound edges.Results. The results of histological study show that experiments with application of bio-implant demonstrated less vascular congestion and interstitial swelling. Phologistic infiltration also responded more efficiently both quantitatively (manifestation rate) and qualitatively (quick change of cell elements) in the group that used bio-implant.Conclusion. Results of morphological studies and pneumocompression data under modelling of duodenal fistulas in experimental animals show that application of bio-implant helps to earlier restore microcirculatory abnormality.